"Subscribe to my channel": The Impact of Digital Influencers on Attitude Towards Brand, Brand Attachement and Purchase Intention - Soares, Priscila Rodrigues Tarlé (2018)
Dissertação de Mestrado em Marketing apresentada à Faculdade de Economia